1998
DOI: 10.1117/12.330398
|View full text |Cite
|
Sign up to set email alerts
|

<title>Nonlinear-optic-polymer-based integrated optoelectronic modulators/switches</title>

Abstract: A new scheme for a nonlinear optical (NLO) polymer opto-electronic (OE) modulator/switch is presented that renders the potential to realize a device interaction length that is an order of magnitude shorter than conventional NLO polymer OE devices operating at TTL voltage levels. It utilizes available NLO polymer materials for the core layer and conductive polymer materials for the cladding layers in order to realize an effective 1 im separation between the electrodes. Using current NLO polymer materials with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Part of the advancement is through the use of relatively more conductive polymers for the cladding layers. [8][9][10][11][12][13][14] For electro-optic (EO) modulators, one wants an electric field induced phase retardation of π or 180°. For a transverse type EO modulator, the voltage necessary to realize this π phase retardation is defined as the half-wave voltage, Vπ, given by 15 where λ is the operational wavelength, d is the thickness of the nonlinear optic core material, n is the refractive index of the EO active core material after electric field poling, r 33 is the electro-optic coefficient of the EO active core material, L is the length of the interaction region, and Γ is the is the modal overlap integral.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Part of the advancement is through the use of relatively more conductive polymers for the cladding layers. [8][9][10][11][12][13][14] For electro-optic (EO) modulators, one wants an electric field induced phase retardation of π or 180°. For a transverse type EO modulator, the voltage necessary to realize this π phase retardation is defined as the half-wave voltage, Vπ, given by 15 where λ is the operational wavelength, d is the thickness of the nonlinear optic core material, n is the refractive index of the EO active core material after electric field poling, r 33 is the electro-optic coefficient of the EO active core material, L is the length of the interaction region, and Γ is the is the modal overlap integral.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research interest has been shifted toward EO waveguide and fibre devices based functional polymers. It has been demonstrated that EO organics have a much higher EO coefficient and faster response than traditional inorganic crystals [11]. Moreover, EO polymers could offer unique and superior characteristics in the design and fabrication of even higher speed devices.…”
Section: Introductionmentioning
confidence: 99%